Monitoring Covid-19 Policy Interventions - Giudici, Paolo; Raffinetti, Emanuela (Frontiers in Public Health, 2020)
To be effective, policy measures aimed at containing the Covid-19 contagion need continuos monitoring of their results, by means of accurate statistical analysis. To this aim we propose an innovative statistical tool, based on the Gini-Lorenz concentration approach, which can reveal how well a country is doing in reducing the growth of contagion, and its speed.